Extracellular Vesicles and Citrullinated Histone H3 in Coronavirus Disease 2019 Patients - Traby, Ludwig; Kollars, Marietta; Kussmann, Manuel; Karer, Matthias; Šinkovec, Hana; Lobmeyr, Elisabeth; Hermann, Alexander; Staudinger, Thomas; Schellongowski, Peter; Rössler, Bernhard; Burgmann, Heinz; Kyrle, Paul A.; Eichinger, Sabine (Thrombosis and Haemostasis, 2021)
Objectives Pulmonary thrombus formation is a hallmark of coronavirus disease 2019 (COVID-19). A dysregulated immune response culminating in thromboinflammation has been described, but the pathomechanisms remain unclear.Methods We studied 41 adult COVID-19 patients with positive results on reverse-transcriptase polymerase-chain-reaction assays and 37 sex- and age-matched healthy controls. Number and surface characteristics of extracellular vesicles (EVs) and citrullinated histone H3 levels were determined in plasma upon inclusion by flow cytometry and immunoassay.Results In total, 20 patients had severe and 21 nonsevere disease. The number of EV (median [25th, 75th percentile]) was significantly higher in patients compared with controls (658.8 [353.2, 876.6] vs. 435.5 [332.5, 585.3], geometric mean ratio [95% confidence intervals]: 2.6 [1.9, 3.6]; p < 0.001). Patients exhibited significantly higher numbers of EVs derived from platelets, endothelial cells, leukocytes, or neutrophils than controls. EVs from alveolar-macrophages and alveolar-epithelial cells were detectable in plasma and were significantly higher in patients. Intercellular adhesion molecule-1-positive EV levels were higher in patients, while no difference between tissue factor-positive and angiotensin-converting enzyme-positive EV was seen between both groups. Levels of EV did not differ between patients with severe and nonsevere COVID-19. Citrullinated histone H3 levels (ng/mL, median [25th, 75th percentile]) were higher in patients than in controls (1.42 [0.6, 3.4] vs. 0.31 [0.1, 0.6], geometric mean ratio: 4.44 [2.6, 7.7]; p < 0.001), and were significantly lower in patients with nonsevere disease compared with those with severe disease.Conclusion EV and citrullinated histone H3 are associated with COVID-19 and could provide information regarding pathophysiology of the disease.
Keywords: COVID-19; extracellular vesicles; NETs; coagulation activation; ARDS; immunothrombosis; citrullinated histone H 3